2017
DOI: 10.19045/bspab.2017.60024
|View full text |Cite
|
Sign up to set email alerts
|

Response of sunflower varieties to NPK fertilization

Abstract: This study was executed at Agriculture Research Institute (ARI) Tarnab (Peshawar) to evaluate the response of sunflower varieties (hybrids) to different combinations of Nitrogen, Phosphorus and Potash (NPK). Four sunflower varieties (hybrids i.e Aritar-93, Peshawar-93, Hysun-33 and SF-187) were sown with five levels of NPK (40:40:40, 80:50:50, 120:60:60, 160:70:70 and 200:80:80 kg ha -1 ) using two factorial randomized complete block design with three replications. With the increase of NPK levels, significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
3
2
0
Order By: Relevance
“…In general, differences between the two locations may be due to soil properties and environmental conditions (Table 1 and fig1). This result agrees with (Ahmad et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In general, differences between the two locations may be due to soil properties and environmental conditions (Table 1 and fig1). This result agrees with (Ahmad et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…The maximum mean value of seed index was founded for (Velko * Super-Nano) at Ranya and Saruchawa locations as compared to the control treatment. Similar results were obtained by Ahmad et al, (2017) they notcied the role of fertilization by NPK on the interactions with sunflower variety, the evidence from the interaction treatment between Fertilizer × Varieties caused maximum value (53.23 g) which noted for variety SF-187 and NPK at the rate of 200-80-80 kg ha -1 . While the minimum weight of a thousand seeds (38.63 g) was noted for the Peshawar-93 variety that was given NPK dose at the rate of 40-40-40 kg ha 1 .…”
Section: Discussionsupporting
confidence: 81%
“…This may be also due to favourable environment and photosynthesis activity which increased the accumulation of dry matter in the plant. This finding is in consensus with those of Ahmad et al (2017) and Emam (2019). The data revealed that harvest index in variety T-397 (39.56%) was significantly higher and was at par with variety JLS-95 (38.38%), RLC-153 (37.08%), Parvati (37.79%) and it was found minimum with variety LSL-93 (32.43%) which was at par with variety Shekhar (34.14%) and Priyam (34.07%).…”
Section: Yield Attributes Of Linseedsupporting
confidence: 92%
“…[14] It has been stated that extracts obtained from this plant affect seed development, germination rates of seeds, and root development. [15] Thuja orientalis is also a plant cultivated primarily for making hedges in parks and gardens and is also used for lumber, construction stakes, railroad ties, musical instruments, and canoe building. [16] Moreover, it contains essential oils that are used for medicinal purposes, including homeopathy and the treatment of diseases such as bronchial catarrh, enuresis, cystitis, psoriasis, rheumatism, and shingles, as well as in various forms of traditional medicine.…”
Section: Introductionmentioning
confidence: 99%